Factors affecting family planning behavior among women in Samarinda, Indonesia - Feriani, Pipit; Yunitasari, Esti; Efendi, Ferry; Krisnana, Ilya; Ernawati, Rini; Sari, Reny Mareta; Tianingrum, Niken Agus; Safaah, Nurus (International Journal of Public Health Science (IJPHS), 2024)
Women are considered to be the most common recipients of contraceptive methods. This study aimed to determine the most influential factors in family planning behavior among women in Samarinda, Indonesia. This study used a cross-sectional design and involved 384 women of childbearing age in the area of Samarinda Primary Health Care. Data were collected using a questionnaire to measure education, income, culture, parity, health workers, and family support for family planning. All variables were categorized and the data were analyzed using binary logistic regression. The significance level was set at 0.05. The study showed that generally respondents have good family planning behaviour (228 respondents; 59.4%) while parity, family support and culture are good in contraceptive use. It is presented that culture support (p=0.004; OR=2.081) become the most dominant factor of contraceptive use behaviour after controlled by education (p=0.047; OR=1.574), income (p=0.043; OR=0.632), parity (p=0.011; OR=0.575) and family support (p=0.025; OR=0.518). Women with a supporting culture will have better contraceptive use behavior than women who do not after controlling for education, income, parity, and family support. It is expected that harmonizing culture with health programs can encourage people to improve their health behaviors.